(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2023)
The total universe is made up of many universes like our own. These different universes can interact in many different ways. These collisions are essential for the development of each of the many universes. Because of this interaction, a process is started so that the landscape structure where the universes develop leads us to different practical values of the cosmological constant. So then, quantum tunneling plays a vital role in the rise of the new areas created by the Universal interacts. This leads to the values of their vacuum state. The interacting universes and the new areas that they create depend on just small regions of Spacetime. The quantum effects are significant only in this Spacetime. These new areas that develop help to develop different areas of a continuous process.